Rules and Values: A Coordinated Regulatory and Educational Approach to the Public Health Crises of Chronic Pain and Addiction - Katzman, Joanna G. (American Public Health Association, 2014)
Chronic pain and opioid addiction are 2 pressing public health problems, and prescribing clinicians often lack the skills necessary to manage these conditions. Our study sought to address the benefits of a coalition of an academic medical center pain faculty and government agencies in addressing the high unintentional overdose death rates in New Mexico. New Mexico’s 2012–2013 mandated chronic pain and addiction education programs studied more than 1000 clinicians. Positive changes were noted in precourse and postcourse surveys of knowledge, self-efficacy, and attitudes. Controlled substance dispensing data from the New Mexico Board of Pharmacy also demonstrated safer prescribing. The total morphine and Valium milligram equivalents dispensed have decreased continually since 2011. There was also a concomitant decline in total drug overdose deaths.